Numerical simulation of outdoor wind environment of typical traditional village in the northeastern Sichuan Basin. (2017) - Zhang, Lili; Hou, Jiawen; Yu, Yan; Du, Junfei; Meng, Xi; He, Qin
Abstract: Since the Guideline of Strengthen Preservation and Development of Traditional Village enacted, the traditional villages gradually gain academic concern and many achievements are acquired. But the study about outdoor wind environment is still insufficient. In this paper, the outdoor wind environment of Liyuanba Village in Bazhong City of Sichuan Province – a typical traditional village in the northeastern Sichuan Basin, is simulated by CFD methods. According to the simulation result, the outdoor wind environment in winter is comfortable for people in general, but there are still eddies and corner flows in some areas. To improve the outdoor wind environment, the suggestions such as changing the direction of courtyard and building are put forward. Furthermore, the optimization is also simulated and these two simulation results are compared in the end.